The Encounter of the Pentecostal Community with the Batu Simbuang Ritual of the Toraja Society: An Exploration within Amos Yong's Intercultural Theology Framework - Agustinus, Agutinus; Wulur, Hersen Geny; Wijaya, Hengki (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This research is an attempt to investigate Amos Yong’s Approach to Intercultural Theology as a framework for bridging Pentecostalism with the Batu Simbuang ritual in the Toraja society. The background of this research is grounded in the perception that Pentecostalism is often seen as having conservative attitudes toward culture. The research found that the roots of Pentecostal doctrine are closely linked to culture. Furthermore, the research shows the presence of shared values between Pentecostalism and the Batu Simbuang ritual, which is a part of Toraja society’s life. The contribution of this research lies in its exploration of Amos Yong's Approach to Intercultural Theology as a framework for fostering connections between Pentecostalism and the Batu Simbuang ritual in Toraja society. By challenging the perception of Pentecostalism as culturally conservative, the research reveals the intricate connection between Pentecostal doctrine and culture.